Functions of Code-switching by English Language Teachers at SMKN 1 Enam Lingkung - Hafif Syukra; Hamzah Hamzah (Universitas Negeri Padang, 2023)
Indonesian people is easily considered as bilinguals, and even, multilinguals. Members of bilingual and or multilingual community are subject to change in their ability to understand the languages they spoke daily. One of the phenomenon can be observed from this is code-switching, whether in trades, offices, and schools. This research aimed to describe the functions of code-switching by English Teachers at SMKN 1 Enam Lingkung. This research was conducted using qualitative-descriptive method. In order to obtain the data necessary for this study, the researcher recorded, transcribed, and tabulated the utterances of English teachers while teaching. The results of the study showed that message qualification has the highest occurrences. It was later followed by reiteration, personalization vs objectivization, addressee specification, and quotation. Interjections as a function of code-switching was not found in this research.